Quality of Life and Symptoms Management in Cancer Patients with Financial Toxicity: A Systematic Review - Ikhsan Sodik; Yati Afiyanti; Hanny Handiyani; Imami Nur Rachmawati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Cancer is a complex disease associated with a wide range of symptoms, declining quality of life, and financial toxicity (FT).To examine the quality of life and symptoms management in Cancer patients experiencing financial toxicity based on a review of published literature.A systematic review was conducted using five databases: Sage Journals, Science Direct, ProQuest, Clinical Key, and Oxford Academic from 2015-2025 years with keywords Quality of Life, Symptom Management and Cancer Patients. The quality of studies was assessed depending on the study design of the 1,050 articles found, only 11 were reviewed. Findings from 11 studies indicated that the quality of life in cancer patients is influenced by multiple factors. Financial toxicity showed a negative correlation with quality of life (r =0.23, p = 0.0057), indicating that higher levels of financial toxicity are associated with lower quality of life. Psychological symptoms such US anxiety and depression were positively associated with FT (r = 0.27, p = 0.0151; r = 0.18, p = 0.0336). High symptom burden, both physical and psychological, significantly reduced quality of life, while social support played a positive role in enhancing well-being (r = -0.17, p = 0.0412). Integrative therapies improved quality of life by 82%, and cost related health literacy was found to reduce financial toxicity (OR = 0.823, p= 0.039). Holistic interventions and attention to the financial challenges faced by cancer patients are essential for improving quality of life, particularly for those affected by financial toxicity. Effective symptom management involves the use of various tools (ESAS, HADS, FACT-G, SESI, EORTC QLQ-C30) and approaches such as palliative care, integrative therapies, symptom cluster management, acupuncture, financial support, social support, enhanced cost-related health literacy, improved psychological resilience, and identification of financial toxicity risks.The quality of life in Cancer patients is influenced by a complex interaction of factors, including financial condition, symptom management, social support, and multidisciplinary care. Enhancing health literacy—especially regarding financial aspects—with comprehensive, evidence-based, and accessible information such as insurance, medication coverage, and financial resources, is critically important.